ANTIOXIDANT ACTIVITY TEST ON KEFIR WHEY WITH TURMERIC NATURAL DYE (Curcuma longa L.) - Rohmah, Nilna Alfa; Estikomah, Solikah Ana; Kurniawan, Kurniawan; Budi Sawitri, Satwika (PC IAI Sragen, 2024)
Excess free radicals in a person's body to exceed the body's ability to manage them can cause a condition called oxidative stress. Oxidative stress is a condition of imbalance between the amount of free radicals present and the amount of antioxidants in the body. One of the Prevention of oxidative stress is by increasing the intake of antioxidants. During this time whey in most cheese companies just becomes a waste. As we know that the Whey contains high nutrients and has health benefits and contains antioxidants. The purpose of this study was to determine the use of cheese whey in kefir whey beverage processed products with turmeric natural dyes that are rich in antioxidants. This study was conducted by an experimental method consisting of 5 (five) stages, namely the first stage of making kefir whey drink with turmeric natural dyes. The second stage is testing pH, the third stage is testing water content, the fourth stage is antioxidant activity testing, the fifth is testing hedonic (liking). The results showed that the variant concentration of cheese whey significantly affect the water content, antioxidant activity and preferences (color, flavor, scent). But there is no real effect on the pH value because the average pH value is the same. Variable pH value, water content and hedonic (preference) does not affect antioxidant activity. So it can be concluded that kefir whey with turmeric natural dye has the potential as a drink that contains antioxidants that can reduce levels and can prevent oxidative stress.